Ruminally protected and unprotected Saccharomyces cerevisiae fermentation products as alternatives to antibiotics in finishing beef steers(1) - Shen, Yizhao (J Anim Sci, 2019)
The objectives of this study were to assess the effects of Saccharomyces cerevisiae fermentation products (SCFP; NaturSafe, SCFPns; and Original XPC, XPC; Diamond V) on growth performance, carcass traits, immune response, and antimicrobial resistance in beef steers fed high-grain diets. Ninety Angus steers (initial body weight [BW], 533 ± 9.8 kg) were assigned to a randomized complete design with 6 treatments (n = 15/treatment): 1) control, 2) low (12 g SCFPns·steer(−1)·d(−1)), 3) medium (15 g SCFPns·steer(−1)·d(−1)), 4) high SCFP (18 g SCFPns·steer(−1)·d(−1)), 5) encapsulated XPC (eXPC; 7 g XPC·steer(−1)·d(−1) encapsulated with 9 g capsule material), and 6) antibiotics (ANT; 330 mg monensin + 110 mg tylosin·steer(−1)·d(−1)). Steers were fed ad libitum a diet containing 10% barley silage and 90% barley grain concentrate mix (dry matter basis) for 105 d. Increasing SCFPns tended (P < 0.09) to linearly increase feed efficiency. Average daily gain (ADG) tended (P < 0.10) to be greater in steers supplemented with eXPC than control. The SCFPns also tended (P < 0.10) to linearly increase marbling score. Proportion of severely abscessed livers tended (P < 0.10) to be lower in steers supplemented with medium and high SCFPns, eXPC, or ANT. A treatment × days on feed interaction were noticed (P < 0.01) for blood glucose, blood urea nitrogen (BUN), and acute phase proteins. The concentration of blood glucose responded quadratically (P < 0.05) on days 28 and 56, whereas BUN linearly (P < 0.01) increased on day 105 with increasing SCFPns dose. The SCFPns linearly increased haptoglobin (P < 0.03) and serum amyloid A (SAA;P < 0.05) concentrations on day 105, and lipopolysaccharide binding protein (LBP;P < 0.01) on days 56 and 105. The percentage of erythromycin-resistant and erythromycin + tetracycline-resistant enterococci was greater (P < 0.05) with ANT than control, SCFPns, and eXPC, whereas no difference was observed among control, SCFPns, and eXPC. No treatment effect was detected on the percentage of tetracycline-resistant enterococci. These results indicate that feeding SCFPns and eXPC was beneficial in improving ADG, feed efficiency and decreasing liver abscesses in a manner comparable to ANT. Unlike antibiotics, SCFPns or eXPC did not increase antimicrobial resistance. Both SCFPns and eXPC are potential alternatives to in-feed antibiotics.